Ten-year results of intense dose-dense chemotherapy show superior survival compared to a conventional schedule in high-risk primary breast Cancer: final results of AGO phase III iddEPC trial - Möbus, Volker; Jackisch, Christian; Lueck, Hans-Joachim; Du Bois, Andreas; Thomssen, Christoph; Kuhn, Walther; Nitz, Ulrike; Schneeweiss, Andreas; Huober, Jens; Harbeck, Nadia; Minckwitz, Gunter von; Runnebaum, Ingo B.; et al. (Annals of oncology, 2018)
dose-dense; high-risk early breast cancer; intense dose-dense
Gesehen am 20.07.2020